A to Z of akhlaaq: moral values for children - Khan, Nafisa; Gurmeet (Goodword Books New Delhi, 2007)
The A to Z of Akhlaaq: Moral Values for Children is a children's book designed to teach essential Islamic moral values through the alphabet. Each letter represents a key ethical trait, such as honesty, kindness, respect, and patience. The book presents these values in a simple, engaging way, using relatable examples and colorful illustrations to help children understand and practice good character in their daily lives. Its aim is to instill a strong foundation of akhlaaq (moral conduct) from an early age, promoting positive behavior in both personal and social settings. 4o